Hua Tuo's Wu Qin Xi (Five Animal Frolics) movements and the logic behind it - Saša Balaneskovic (Wolters Kluwer Health/LWW, 2018)
The key proposition of this hypothesis is logic behind the order of movements of Hua Tuo's qigong Wu Qin Xi (Five animal frolics). To date, there were many discussions about connection of the movements of Wu Qin Xi with existing TCM theories and why Hua Tuo made it in that particular way. Some experts are saying that there is no connection but if all stories of Hua Tuo's abilities and knowledge were half-truth, he wouldn't let even the order of movements of qigong that he created be just a random order. Hypothesis is exploring different views on Taiji movement direction, Wu Xing and connection between animals in Wu Qin Xi, Lo Shu square and Sun wheel and proposing possible solution to the question "Why Hua Tuo made such order of animals in Wu Qin Xi?" by analyzing and and cross referencing the common ground between theories and bridging the gap the we were left without any written explanation from the master itself. Further progress and confirmation of this hypothesis requires deeper research and cooperation between Qigong expert historians.